The involvement of Polish teachers of English in teaching target language culture - Zybert, Jerzy (Scripta Neophilologica Posnaniensia, 2019)
The present paper discusses the current perception of the concept of culture with relation to FL students’ needs. It explores the extent to which Polish teachers of English are aware of the significance of teaching target culture and reports on its actual implementation in the language classroom. Comments on the present situation and suggestions for improving it are provided.